In Vitro Antioxidant Activity and Hepatoprotective Potential of Ceropegia spiralis Against Paracetamol Induced liver injury - Rajkiran Kolakota, R. Santosh Kumar, Sunil Kumar Patnaik (Journal of Applied Pharmaceutical Science, 2017)
Ceropegia spiralis is a usually used remedial herb in herbal remedies to delight diverse diseases. The plan of the current investigation is to assess the in vitro free radical scavenging activity and hepatoprotective activity of Ceropegia spiralis against paracetamol induced liver damage in preventive and curative models. The Ceropegia spiralis was evaluated for in vitro antioxidant activity by 2, 2-diphenyl-1-picryl hydrazyl (DPPH), hydroxyl and superoxide radical scavenging activity and inhibition of lipid peroxide and ascorbic acid was used as a standard. In two separate studies, the 100, 200 and 400 mg/kg body weight of Ceropegia spiralis extract, and 100 mg/kg body weight of Silymarin in both studies were given orally. The hepatic damage was done by oral administration of 2 g/kg body weight of paracetamol. The IC50 values of Ceropegia spiralis in the superoxide, 2, 2-diphenyl-1-picryl hydrazyl (DPPH), hydroxyl radical scavenging activity and inhibition of lipid peroxidation was found to be 365.64, 381.13, 461.32 and 469.39 μg/ml correspondingly. The hepatic damage in rats induced by paracetamol as evidence by elevated serum aspartate aminotransferase (AST), alanine aminotransferase (ALT), alkaline phosphatase (ALP) and total bilirubin levels and decreased serum total proteins. The administration of Ceropegia spiralis and Silymarin in both preventive and curative models decreases the toxic effect of paracetamol on the above selected serum parameters.
Keywords: Ceropegia spiralis, Antioxidant, Paracetamol, Hepatoprotective, Rat.